Analisis Kompetensi Kepribadian Guru Kelas IX di SMP Negeri 23 Medan - Johannes Tamba; Pebi Fauziyana Br Tarigan; Putri Isnaini; Sani Susanti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the personality competence of ninth-grade teachers at SMP Negeri 23 Medan based on students' perceptions. The research employed a qualitative descriptive approach with data collected through observation and in-depth interviews involving nine purposively selected students. The findings reveal that most teachers demonstrated basic aspects of personality competence, such as punctuality and responsibility. However, several issues were identified, including emotional instability in handling classroom situations, favoritism, and the use of physical punishment as a disciplinary method. These findings indicate that teachers' personality competence still needs improvement, particularly in emotional regulation, fairness, and role modeling. The study recommends structured and continuous personality development programs for teachers to foster a positive classroom environment and support students' character development.